Design of indirect ELISA-based test-system for determination of Mannheimia haemolytica antibody titre in bovine sera - Ye. S. Kostrova; O. P. Bjadovskaya; Ye. V. Peshkova; O. V. Pruntova (Ветеринария сегодня)
Indirect ELISA-based test-system was developed for determination of Mannheimia haemolytica antibody titre in sera from cattle of different age-sex groups. Lipopolysaccha-ride antigen (LPS-antigen) produced by phenol-water extraction from Mannheimia haemolytica strain No. 29696 (ATCC collection) was used as an antigen. Results obtained during the comparative examination of bovine sera using the proposed test-system and commercial test-system «Mannheimia haemolytica ELISA KIT» (BIOX, Belgium) are demonstrated. Relative specificity and sensitivity of the designed method were determined.